Explaining the Mexican-American health paradox using selectivity effects - Ernesto Aguayo Téllez; José N. Martínez; Erick Rangel González (Banco de México, 2015)
While typically socioeconomically disadvantaged, Mexican migrants in the United States tend to have better health outcomes than non-Hispanic Whites. This phenomenon is known as the Hispanic Health Paradox. Using data from Mexico and the United States, we examine several health outcomes for non-Hispanic Whites and Mexicans in the United States and in Mexico and employ Blinder-Oaxaca decompositions to help explain the paradox. We find evidence that selectivity is playing a significant role in the relatively healthy status of Mexican migrants in the United States. More importantly, there is evidence that health selectivity is a complex process and its effects typically do not work the same way for different health conditions and across genders. We also find evidence that some of migrants' health advantages are lost as they spend more time in the United States.
Keywords: I10; F22; O15; 330; International Migration; Mexico; Selectivity; Health Paradox